The Role of Art in Promoting Tourism in the Province of West Nusa Tenggara (NTB) - Biagi, I Wayan Kusuma Di; Suryadmaja, Galih; Renda, Rapi; Nahdlatuzzainiyah, Nahdlatuzzainiyah; Wangi, Baiq Larre Ginggit Sekar (Jurnal Multidisiplin Sahombu, 2025)
This study aims to identify the various roles of art in promoting tourism in West Nusa Tenggara (NTB). It explores different forms of art and how they can be utilized to attract tourists, as well as analyzing the impact of art on the number of tourist visits. The research employs a qualitative approach to gain an in-depth and comprehensive understanding of the social and cultural phenomena related to the role of art in tourism promotion in NTB Province. The data collected from the field are then analyzed thematically by identifying patterns and themes that emerge. The findings of this study reveal that art, including performing arts, visual arts, and traditional arts, significantly contributes to attracting tourists. The integration of art into tourism promotion also supports the preservation of local culture. Overall, traditional arts in West Nusa Tenggara not only serve an aesthetic function but also play a central role in promoting tourism, cultural education, and the local economy. The results of this research provide valuable insights for local governments in formulating policies and strategies for tourism development. By understanding the role of art in tourism promotion, governments can more effectively allocate resources and support artistic activities that attract tourists.